Medical advice for baby swimmers - O'Brien, M.; Smith, J.; Bolger, M. (Biomechanics and Medicine in Swimming, 1983)
Hydrotherapy has been used for many years to improve muscle tone and coordination in babies and adults (Davis, 1967; Duffield, 1976; Newman, 1975). Babies exposed to graded exercise in warm swimming pools improve in coordination and gain physical, mental and social skills exceeding those observed in their peers (Quinn, 1981). Children born and brought up in the tropics often swim before they can walk and learn this skill before they have acquired a fear of water. In Ireland baby swimming has been pioneered by international swimming coach Jack Smith, who started baby swimming classes in a private school 3 years ago. In September 1980 other baby swimming classes were started, one in Dublin and one in Belfast. In 1982 the public pools set aside hours for mother and baby swimming but had no organized teaching. Because of the great interest that has arisen, the Northern Ireland Sports Council and its equivalent body, Cospoir, in the Republic, in association with the Education Committee of the Irish Amateur Swimming Association, currently are providing guidelines to be used by leisure centers and swimming pools wishing to provide facilities for baby swimming.